Aplicación del programa de estimulación "NIÑOS FELICES" basado en el constructivismo para favorecer el desarrollo de la lecto escritura en niños y niñas de 5 años de l.E.I Nº 314 "Sector Rupacucha" - Rioja año 2008 - Damián Irigoin, Evelyn Elizabeth (2010)
The present investigation arose as product of the observation of the local, regional educational context and mainly at institutional level. Experts of the problem of the teaching - learning of the reading and the writing in the level of initial, intended the investigation whose objective is to determine the effects that produces the stimulation program "Happy Children" in the lectoescritura development in children and girls of five years of age of the lnitial Educational Institution Nº 314, located in the sector Rupacucha, of the county of Rioja. In this sense, on the base of the theoretical mark, the investigation hypothesis was formulated under the supposition that the application of the one -e 'erred program stimulates the learning of the lectoescritura significantly, for that which had a sample of 8 children and 10 girls of five years of age of the referred lnstitution Educational lnitial. The applied type investigation was driven under a design preexperimental, with pre and postest whose data were processed and they presented in squares and graphics. The contrastación of the hypothesis was carried out by means of the aplication of the test t - student for the difference paired with a level of trust of 95%. As for the results, it was demonstrated that the children and girls of five years of age of the lnitial Educational lnstitution Nº 314, located in the sector “Rupacucha", when being stimulated by means of the program "Happy Children", they evidenced a significant development in the lectoescritura, the same as in each one of the dimensions: reading and it notarizes. For the investigation it means that the children that presented a learning level at the beginning of the investigation in "I begin" and in "I process", they improved significantly after being stimulated with the stimulation program until arriving at the level of "I Achieve foreseen"